Effects of temperature in the development and survival of the mealybug Pseudococcus longispinus (Targioni Tozzeti, 1867) (hemiptera: pseudococcidae) in coffee plants - Santa-Cecília, Lenira Viana Costa; Prado, Ernesto; Sousa, Marcella Viana de; Sousa, Ana Luiza Viana de; Correa, Lilian Roberta Batista (Coffee Science - ISSN 1984-3909, 2011)
The mealybug Pseudococcus longispinus (Targioni Tozzetti, 1867) (Hemiptera: Pseudococcidae) has been reported attacking coffee crops and causing fruit fall in the State of Minas Gerais, Brazil. The knowledge of its biology is necessary to implement control measures. Its development was studied at temperatures of 15, 20, 25, 30 and 35ºC. The insects were confined inside a Petri dish containing a foliar disc of 4 cm diameter of Coffea arabica L., cultivar 'Acaiá Cerrado'. The temperature affected the P. longispinus development and survival. Few insects reached the final stage at temperatures of 15 and 30°C, and 100% of mortality was obtained at 35ºC. The duration of the nymphal stage was reduced when the temperature was risen from 20 to 25ºC, with a survival rate of 80% on both temperatures. The thermal requirements varied according to the development stage of the mealybug. The base temperature was fixed at 8.0 ºC for the nymphal stage of females and a thermal constant of 422.1 day degrees. The number of generations increased with the temperature. The optimal temperature for the insect development was 25ºC.